Unexpected effects of inorganic phosphate glass on crystallization and thermo-rheological behavior of polyethylene terephthalate. (10th October 2018) - Kim, Kyoungtae; Kashani Rahimi, Shahab; Alam, Todd M.; Sorte, Eric G.; Otaigbe, Joshua U.
Abstract: The effects of ultra-low glass transition temperature (Tg ) phosphate glass (Pglass) on the thermal, morphological, rheological, mechanical, and crystallization properties of hybrid Pglass/poly(eththylene terephthalate)(PET) were investigated. Nano- and micro-scale distribution of the Pglass in the PET polymer matrix was observed. The polydispersed Pglass in the PET matrix functioned as a nucleation agent, resulting in increasing crystallization temperature. The Pglass in the PET matrix decreased the Tg, indicating a plasticizing effect of the Pglass in the hybrids that was confirmed by the significantly decreased complex viscosity of the PET matrix. In addition, with increasing temperature, a non-terminal behavior of the viscoelastic properties occurred due to the hybrid structural changes and improved miscibility of the hybrid components. Further, the obtained solid-state variable temperature 31 P and 1 H NMR spectroscopy results showed strong Pglass concentration dependency of the interactions at the PET-Pglass interface. Graphical abstract: Highlights: Ultra-low glass transition temperature Pglass was polydispersed in nano- to micro-scale in the PET polymer matrix with improved properties. The higher crystallization temperature is ascribed to the special polymer crystal nucleation effect of Pglass in the hybrid materials. The viscoelastic material functions confirmed the special ability of the Pglass to significantly plasticize the PET with enhanced benefits. Increasing the melt temperature improved the PET-Pglass miscibility, resulting in non-terminal rheological behavior of the hybrid materials.